Optimization of truss structures based on member dispositions / Associate Prof. Dr. Wahyu Kuntjoro and Jamaluddin Mahmud - Kuntjoro, Wahyu (Associate Prof. Dr.); Mahmud, Jamaluddin (2005)
A design is optimum if a certain design objective function is minimum (or maximum), and still meets its design requirements. Truss structures can be optimized by deleting members which do not contribute significantly or at all to load carrying capacity. Through conventional member size optimization, non performer members can be identified, and then removed. Strength and displacement were formulated as the design constraints while the weight of structure was formulated as the objective function. The Linear Extended Interior Penalty Function was employed to optimize the structure. Finite Element Analysis, together with an approximation procedure were used to obtain the truss structural responses. This paper describes the development of truss optimization through members deletion. Three-bar and six-bar truss structures were used as case studies. Results showed that the truss disposition could be optimized using members deletion strategy.